IMMU-28. DECIPHERING THE AT/RT LIGANDOME. Issue 2 (22nd June 2018) - Marcu, Ana; Trautwein, Nico; Stevanovic, Stefan; Johann, Pascal; Technau, Antje; Lager, Johanna; Monoranu, Camelia-Maria; Henkel, Lisa; Krauß, Jürgen; Ebinger, Martin; Schuhmann, Martin; Thomale, Ulrich; et al.
Abstract: Atypical teratoid/rhabdoid tumors (AT/RTs) are commonly regarded as immunologically cold tumors, as they rank among malignancies with the lowest mutational load. However, low mutational burden is not necessarily correlated with poor immunogenicity, as tumor-exclusive peptides bound in the tumor cell's MHC represent potential targets for immune responses. Indeed, in a first set of n=17 AT/RT samples we could determine by immunohistochemistry that 1.8% of all cells within the tumors were T-cells. MHC class I, class II, and PD-L1 was expressed on 12.9%, 3%, and 5.1% of the tumor cells, respectively. To investigate whether the ligandome of AT/RTs contained tumor-exclusive peptides we then analyzed 23 centrally reviewed AT/RTs using LC-MS and subsequent bioinformatical validation. In 14 (61%) and 21 (91%) of the 23 patients, tumor-exclusive peptides were identified (59 MHC class I and 153 class II peptides in total). Of these, 47/109 peptides were exclusive for one tumor, demonstrating the high individuality of the AT/RT ligandome. Representative examples of these ligandome peptides proved to be immunogenic in T-cell priming assays. Mutation analysis revealed a median of 11 (range 1-166) tumor-specific mutations dispersed over the entire genome. In silico MHC-binding prediction showed that these neoantigenic peptides had a similar binding affinity compared to their ligandome counterparts. In conclusion, tumor-exclusive ligandome peptides can be identified in the vast majority of AT/RT patients. In silico and in vitro analyses qualify them as suitable candidates for personalized cancer vaccines.